PREECLAMPSIA AND ECLAMPSIA: PROSPECTS FOR DIAGNOSTICS AND PREVENTION - Юрий Алексеевич Петров; Анастасия Дмитриевна Купина (The Publishing House Medicine and Enlightenment, 2020)
The aim of the research - to carry out an analytical review of modern sources of scientific literature covering the issues of epidemiology, pathogenesis, new methods of diagnosis, treatment and prevention of preeclampsia and eclampsia in pregnant women. Materials and methods. The analysis of 42 domestic and foreign sources of literature on this topic. Results. According to the scientific analysis, the understanding of the pathogenesis of preeclampsia and eclampsia has been updated. The review describes the possible complications of pregnancy and childbirth associated with this pathology, highlights the issues of early and effective ways to verify the disease in pregnant women and methods of preventing this disease. Conclusion. Preeclampsia and eclampsia are associated with a high risk of developing various obstetric complications up to the death of the mother and fetus, which makes these the urgent problem. The analysis shows that modern methods of diagnosis and prevention of this disease will improve the outcome of pregnancy and maintain the health of the mother and fetus.